2009
DOI: 10.1007/s10661-008-0722-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nitrate concentration in groundwater in Saudi Arabia

Abstract: Contamination of groundwater by nitrate is considered a global problem. Nitrates are introduced in the groundwater from a variety of sources like agricultural activities, poor sewer system, wastewaters, and industrial activities. In the present research, a survey of wells (n = 1,060) was undertaken in all 13 regions of the Kingdom of Saudi Arabia to assess the contained nitrate (NO(3)) levels. The results indicated variation in nitrate levels from 1.1 to 884.0 mg/L as NO(3) throughout the Kingdom. The average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Studies have shown that excessive use of fertilizers in agriculture and insufficient sewer systems are causing surface and groundwater pollution globally [1,2]. Assessments of groundwater aquifers made in Portugal, Iran, Saudi Arabia, France, and other countries have shown that in many cases, nitrate (NO 3 − ) concentrations are exceeding the safe drinking water threshold of 50 mg NO 3 − L −1 , which is specified by the World Health Organization [3][4][5][6][7][8]. High NO 3 − concentrations in surface water and groundwater are causing environmental problems, such as eutrophication [9], and since NO 3 − becomes toxic to humans at concentrations of 50 mg NO 3 − L −1 and above, this relates to health issues like methemoglobinemia and cancer [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that excessive use of fertilizers in agriculture and insufficient sewer systems are causing surface and groundwater pollution globally [1,2]. Assessments of groundwater aquifers made in Portugal, Iran, Saudi Arabia, France, and other countries have shown that in many cases, nitrate (NO 3 − ) concentrations are exceeding the safe drinking water threshold of 50 mg NO 3 − L −1 , which is specified by the World Health Organization [3][4][5][6][7][8]. High NO 3 − concentrations in surface water and groundwater are causing environmental problems, such as eutrophication [9], and since NO 3 − becomes toxic to humans at concentrations of 50 mg NO 3 − L −1 and above, this relates to health issues like methemoglobinemia and cancer [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of water deteriorates with heavy metals, nitrate and radioactive elements present in it (Camargo and Alonso, 2006;Nikolaidis et al, 2008). There have been numerous instances of high nitrate level in groundwater across the world due to the agricultural activities (Alabdula'aly et al, 2010;Bernhard et al, 1992;Levallois et al, 1998;Spalding et al, 2001;Wang et al, 2015;Zhang et al, 1996). Several cases of high concentration of nitrate exceeding the threshold limit of 50 mg l -1 for drinking water have been reported in countries like the UK, Denmark, Belgium, France, the USA and India (Agrawal et al, 1999;Banks and Soldal, 2002;Fried, 1991;Hudak, 2000;Strebel et al, 1989;Nolan et al, 1997;Singh et al, 2006;Wakida and Lerner, 2005).…”
Section: Water Quality and Industrial Sourcesmentioning
confidence: 99%
“…It reflects mainly nitrate impact. However, contamination by wastewater was recorded from pit latrines, leakage from the unrehabilitated sewage system, and to some extent animal feedlots and dairies, especially in the high-density housing settlements in Sabya and Jazan cites (Alabdula'aly et al 2010). It is observed that shallow wells contain higher nitrate than deeper ones.…”
Section: Factor Analysismentioning
confidence: 99%